Exploration of associations between the FTO rs9939609 genotype, fasting and postprandial appetite-related hormones and perceived appetite in healthy men and women. (1st November 2019) - Goltz, Fernanda R.; Thackray, Alice E.; Varela-Mato, Veronica; King, James A.; Dorling, James L.; Dowejko, Monika; Mastana, Sarabjit; Thompson, Julie; Atkinson, Greg; Stensel, David J.
Abstract: Background: The fat mass and obesity-associated gene (FTO) rs9939609 A-allele has been associated with obesity risk. Although the exact mechanisms involved remain unknown, the FTO rs9939609 A-allele has been associated with an impaired postprandial suppression of appetite. Objectives: To explore the influence of FTO rs9939609 genotype on fasting and postprandial appetite-related hormones and perceived appetite in a heterogeneous sample of men and women. Design: 112 healthy men and women aged 18-50-years-old completed three laboratory visits for the assessment of FTO rs9939609 genotype, body composition, aerobic fitness, resting metabolic rate, visceral adipose tissue, liver fat, fasting leptin, and fasting and postprandial acylated ghrelin, total PYY, insulin, glucose and perceived appetite. Participants wore accelerometers for seven consecutive days for the assessment of physical activity and sedentary behaviour. Multivariable general linear models quantified differences between FTO rs9939609 groups for fasting and postprandial appetite outcomes, with and without the addition of a priori selected physiological and behavioural covariates. Sex-specific univariable Pearson's correlation coefficients were quantified between the appetite-related outcomes and individual characteristics. Results: 95% confidence intervals for mean differences between FTO rs9939609 groups overlapped zero in unadjusted and adjusted general linear models for all fasting ( P  ≥ 0.28) and postprandial ( P  ≥ 0.19) appetite-related outcomes. Eta 2 values for explained variance attributable to FTO rs9939609 were <5% for all outcomes. An exploratory correlation matrix indicated that associations between fasting and postprandial acylated ghrelin, total PYY and general or abdominal adiposity were also small (r = −0.23 to 0.15, P  ≥ 0.09). Fasting leptin, glucose and insulin and postprandial insulin concentrations were associated with adiposity outcomes (r = 0.29 to 0.81, P  ≤ 0.033). Conclusions: Associations between the FTO rs9939609 genotype and fasting or postprandial appetite-related outcomes were weak in healthy men and women.